2021
DOI: 10.4254/wjh.v13.i12.2113
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral vancomycin in children with autoimmune liver disease: A single centre experience

Abstract: BACKGROUND Previous reports showed some beneficial effect of oral vancomycin treatment (OVT) in children with primary sclerosing cholangitis; conversely, the experience in patients with other autoimmune liver diseases (AILD), including autoimmune hepatitis (AIH) and autoimmune sclerosing cholangitis (ASC), is scant. AIM To assess the response to immunosuppressive treatment (IS) and to OVT in children diagnosed with AILD. METHODS Retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(60 reference statements)
1
0
0
1
Order By: Relevance
“…A recent study of liver samples showed that immune cell alteration, which is responsible for the occurrence of CCA, is higher in patients with PSC and active colitis than in patients with PSC and inactive colitis or PSC without colitis, suggesting a possible role of the microbiota in the association between colitis, PSC, and CCA etiopathogenesis in these patients [68]. In line with this hypothesis, these data may support the idea that antibiotics may represent a possible therapy for patients with colitis and PSC [76,77]. Indeed, treatment with oral vancomycin, which re-equilibrates the species of the gut microbiota, has been shown to improve liver enzymes and the natural history of biliary disease in patients with colitis and PSC.…”
Section: Microbiota and Biliary Tractsupporting
confidence: 67%
“…A recent study of liver samples showed that immune cell alteration, which is responsible for the occurrence of CCA, is higher in patients with PSC and active colitis than in patients with PSC and inactive colitis or PSC without colitis, suggesting a possible role of the microbiota in the association between colitis, PSC, and CCA etiopathogenesis in these patients [68]. In line with this hypothesis, these data may support the idea that antibiotics may represent a possible therapy for patients with colitis and PSC [76,77]. Indeed, treatment with oral vancomycin, which re-equilibrates the species of the gut microbiota, has been shown to improve liver enzymes and the natural history of biliary disease in patients with colitis and PSC.…”
Section: Microbiota and Biliary Tractsupporting
confidence: 67%
“…Bir çalışmada, oral vankomisin tedavisinin standart immünsupresif tedaviye yanıt vermeyen hastalarda biyokimyasal remisyon elde etmek için bir tedavi seçeneği olabileceği ve bu konuda ileriye dönük çalışmalara ihtiyaç olduğu belirtilmiştir. 29 Bir diğer çalışmada, anti-B hücre ve anti-CXCL10 tedavi denemelerinin yeni tedavi ajanları için umut verici olduğu bildirilmiştir. Bu bulgularla çoğu pediatrik hastayı ömür boyu immünosupresan tedavi ve bunların olumsuz yan etkilerinden kurtarmak için intrahepatik gen ekspresyonu ve klinik sonuçlarına ilişkinin gelecekte yeni çalışmalara ihtiyaç olduğu belirtilmiştir.…”
Section: Discussionunclassified
“…V recentních studiích došlo k normalizaci transamináz a sedimentace u pacientů léčených perorálně podávaným vankomycinem v dávce 50 mg/kg/den, přičemž délka léčby byla variabilní. (2,20,21) Nicméně data týkající se jeho paušálního použití jsou zatím limitovaná.…”
Section: Terapieunclassified